Time Preferences, Study Effort, and Academic Performance - Arjan Non; Dirk Tempelaar (Center for Economic Studies and ifo Institute (CESifo), 2015)
We analyze the relation between time preferences, study effort, and academic performance among first-year business and economics students. Time preferences are measured by stated preferences for an immediate payment over larger delayed payments. Data on study efforts are derived from an electronic learning environment, which records the amount of time students are logged in, the number of exercises generated, and the fraction of topics completed. Another measure of study effort is participation in an online summer course. We find no statistically significant relationship between impatience and study effort. However, we find that impatient students obtain lower grades and fail final exams more often, suggesting that impatient students are of lower unmeasured ability. Impatient students do not seem to have severe selfcontrol problems, as they do not earn significantly fewer study credits, nor are they more likely to drop out as a result of earning fewer study credits than required.
Keywords: D03; D90; I21; 330; time preferences; education; study effort; academic performance